Faunos en los trópicos: modernismo y virilidad - Hernández Rodríguez, Rafael (Ecos y resplandores helenos en la literatura hispana: siglos XVI-XXI, 2018, ISBN 978-84-697-9697-9, págs. 113-130, 2018)
Modernism represents an artistic movement that mirrors the changing society of the late 19th century. This changing society produced the first cultural and artistic movement in Spanish America that asked what was this region's place in the Western World as well as what the poet's new function was. Among other issues that revea) the modernity of the movement, such as urbanization, industrialization, or the role of women, there is one of capital importance: the view of masculinity. This essay focuses on three texts that review the image of masculinity and art thought the figure of the faun. El modernismo representa un movimiento artístico que refleja la sociedad cambiante de finales del siglo XIX. Esta sociedad cambiante genera el primer movimiento cultural y artístico continental de importancia que intenta responder a la pregunta ¿cuál es el lugar de Hispanoamérica en el mundo occidental y cuál es la nueva función del poeta? Entre otros aspectos que señalan la modernidad del movimiento (como el urbanismo, la industrialización, el papel de la mujer), hay uno de particular importancia: la revisión de la masculinidad. Este ensayo se centra en tres textos que revisan la visión de la masculinidad y el arte a través de la imagen del fauno.
Section: Ecos y resplandores helenos en la literatura hispana: siglos XVI-XXI
Keywords: dept.wll

De Connecticut a Salamanca: SCSU Program in Spain, 1990-2015, 25 Years of International Education Making a Difference - Arboleda, Carlos Arturo (Southern Connecticut State University, 2016)
Keywords: Connecticut; Southern Connecticut State University; International education; Spain; International education; dept.wll; faculty_collection

Los Que Sobran = Those Not Spared - Barros, Pía (Asterión, 2010)
Keywords: 21st century; 21st century; Chilean fiction; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; Women authors; Chilean fiction; dept.wll; faculty_collection

The impact of Don Quixote (1605-2005) on the culture of the modern and postmodern world: proceedings of the Southern Connecticut State University International Conference on Don Quixote, New Haven, April 22-23, 2005 - Southern Connecticut State University International Conference on Don Quixote New Haven, Conn) (Southern Connecticut State University, 2006)
Keywords: Cervantes Saavedra; Miguel de; 1547-1616. Don Quixote; Congresses; Postmodernism; dept.wll; faculty_collection

Una Poética De La Despreocupación: Modernidad E Identidad En Cuatro Poetas Latinoamericanos - Hernández Rodríguez, Rafael (Editorial Cuarto Propio, 2003)
Keywords: 20th century; Bandeira; Manuel; 1886-1968; Criticism and interpretation; Andrade; Carlos Drummond de; 1902-1987; Criticism and interpretation; Latin American poetry; Criticism and interpretation; Pellicer; Carlos; 1899-1977; Criticism and interpretation; Villaurrutia; Xavier; 1903-1950; History and criticism; Modernism (Literature); Latin America; Identity (Philosophical concept) in literature; dept.wll; faculty_collection

Readings of “Hum dekhenge” by faiz ahmed faiz. Islamic images, revolution, or anti-Hindu sentiments? - Meagher, G.C. (Estudios de Asia y Africa, 2021)
This article examines the controversy caused by the Faiz Ahmed Faiz’s poem “Hum Dekhenge” during the protests triggered by the approval of the Citizenship Amendment Act and the National Registry of Citizens at the end of 2019 in India. In addition to a Spanish translation of the actual text, it also offers a background of the debate, a biographical sketch of the poem’s author, and diverse interpretations. The production of meaning is a complex articulation between text, readers, and the sociopolitical context. “Hum Dekhenge” is a poem of various linguistic, literary, and political registers. Without question its reading is open to multiple possibilities. © 2021. Estudios de Asia y África.
1 citations (Crossref) [2023-10-31] Type: Review tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85113945952
Keywords: dept.wll

Ecocrítica Poscolonial Y Literatura Moderna Latinoamericana - Flores, William (Universidad Nacional Mayor de San Marcos, Fondo Editorial, 2015)
Keywords: 21st century; History and criticism; Ecocriticism; Latin America; Ecocriticism in literature; Postcolonialism in literature; Environmentalism in literature; Ecology in literature; Latin American fiction; dept.wll; faculty_collection

María Elena Gertner: Conversación en torno a la literatura - Cardone, Resha Sophia (Revista Chilena De Literatura, 2016)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/046-573-470-770-155 tex.type: [object Object]
Keywords: dept.wll

Developing cultural humility through critical service learning - Breda, Karen Lucas; Groot, Kim; Towle, Antoinette (Ciencia y enfermería, 2013)
Marked inequities or disparities in health care and health outcomes exist for millions in the United States of America. Urban apartheid and increasing social stratification separate social groups making it difficult for them to understand each other. Many U.S. health care professionals, including nurses, hold negative stereotypes toward the urban poor and disenfranchised. Creating vehicles for understanding and respect between health care professionals and the social groups they care for is needed. Cultural humility uses self-reflection, self-critique, openness and transcendence to address power inequities between providers and clients. "Critical service-learning" is a type of "service-learning" that adopts the tenets of critical theory and pedagogy in engaged partnerships to foster social responsibility and a justice-oriented framework. The purpose of this article is to showcase Project Horizon, an innovative university-based health and social advocacy partnership that uses critical service learning with the urban community to foster cultural humility. Project Horizon outcomes show that this long-term engaged partnership is an effective vehicle for developing and enhancing cultural humility among health care professionals participating in the endeavor. Implications: Replication of social and health advocacy projects such as the one conducted through Project Horizon can be made in other settings to increase the capacity for democratically oriented nurses and other health care professionals who have an enhanced sense of cultural humility.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/076-789-415-089-173
Keywords: Critical service learning; Cultural humility; Health consortia; Health personnel; Healthcare disparities; dept.wll

El silencio abyecto en la plaza del diamante - Weng, Miaowei (Boletín Redipe, 2018)
The article examines the gender roles imposed on women in Spain under the Franco regime. It revisits Mercè Rodoreda’s 1962 novel The Time of the Doves and deciphers the female protagonist’s silence in the context of the post-Civil War period. Drawing on Julia Kristeva’s conception of the abject, it explores how silence becomes informative of the protagonist’s mental resistance to the patriarchal imposition, the helplessness and powerlessness a common woman feels under the Franco regime, and the gradual growth of female subjectivity.
Citation Key Alias: lens.org/044-785-931-144-539, pop00351
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found